2005
DOI: 10.1111/j.1365-2591.2005.01029.x
|View full text |Cite
|
Sign up to set email alerts
|

Apical extrusion of intracanal bacteria following use of two engine‐driven instrumentation techniques

Abstract: Both engine-driven nickel-titanium systems extruded bacteria through the apical foramen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
68
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(73 citation statements)
references
References 28 publications
1
68
0
4
Order By: Relevance
“…However, it is important to point out that periodontal ligament inflammation is multifactorial; and it may be influenced by several features of root canal preparation, such as mechanical stress, debris and/or irrigant extrusion, and apical patency verification (12)(13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is important to point out that periodontal ligament inflammation is multifactorial; and it may be influenced by several features of root canal preparation, such as mechanical stress, debris and/or irrigant extrusion, and apical patency verification (12)(13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…It also has been shown that all root canal preparation techniques cause some degree of debris extrusion (11,(13)(14)(15)(16). However, the amount of apically extruded irritants may vary according to the technique and the characteristics of the instrument used (3).…”
mentioning
confidence: 99%
“…All the preparation methods have showed varying degrees of extrusion, [2][3][4][5][6][7] attributed to various factors such as root canal anatomy, irrigation method, amount/flow rate, penetration depth of irrigant, and selected file type or instrumentation method. Common findings showed that methods involving a push-pull filing motion usually create a greater debris extrusion than engine-driven rotary motion.…”
Section: Introductionmentioning
confidence: 99%
“…Sterilized glass vials were entirely filled with 10 mL of 0.9% saline solution (NaCl). Then, each stopper together with a tooth and needle was placed to its Eppendorf tube, and the tubes were fitted into vials (10). The test apparatus was shown in figure 1.…”
Section: Test Apparatusmentioning
confidence: 99%